PVA-based oxygen-permeable and moisture-permeable strain sensor and preparation method thereof

By combining modified PVA raw materials and bamboo charcoal powder and other materials, gel thin film resistor sheets with high oxygen permeability and high conductivity were prepared, which solved the problem of insufficient oxygen permeability and moisture permeability in emerging technical fields, and realized strain sensors suitable for wearable devices and other fields.

CN119594840APending Publication Date: 2025-03-11BEIJING INSTITUTE OF GRAPHIC COMMUNICATION +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411768753.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing strain sensors cannot meet the requirements of high oxygen permeability and high moisture permeability in emerging technology fields such as wearable devices.

Method used

PVA powder is used as the basic raw material, and modified bamboo powder, graphene oxide and silane coupling agent are blended with high-mixed extrusion to obtain modified PVA raw material. Combined with bamboo charcoal powder and thiophene derivatives, gel thin film resistor sheets with conductive ability are prepared, and in-situ solid polymerization is carried out under atmospheric pressure plasma to enhance its conductive ability and strength.

Benefits of technology

The preparation of PVA-based oxygen-permeable and moisture-permeable strain sensor has high oxygen-permeable performance, suitable strength and high conductivity, which meets the application needs of emerging technology fields.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a PVA-based oxygen-permeable and moisture-permeable strain sensor and a preparation method thereof, and the preparation method comprises the following steps: S1, preparing a modified PVA raw material: uniformly mixing PVA powder, modified bamboo powder, graphene oxide and a silane coupling agent, and then carrying out blending extrusion to obtain a granular raw material; s2, PVA dispersion liquid preparation: mixing and grinding bamboo charcoal powder and a dispersing agent in water, filtering, adding a modified PVA raw material into filtrate, and dissolving to obtain the PVA dispersion liquid; s3, preparing a gel thin-film resistor disc: putting the dispersion liquid into a mold, repeatedly freezing and thawing to obtain thin-layer gel, applying pressure by using a pressing block in a closed cavity, and controlling the humidity to obtain the gel thin-film resistor disc; and S4, in-situ conductivity enhancement: immersing the gel thin-film resistor disc into an ethanol solution of thiophene derivatives and iodine, taking out the gel thin-film resistor disc after the gel thin-film resistor disc is immersed, drying, and carrying out in-situ solid-state polymerization, so as to obtain the gel thin-film resistor disc. And S5, electrode fixation: fixing conductive electrodes at two ends. The strain sensor has the advantages that the obtained strain sensor has relatively high oxygen and moisture permeability and also has proper strength and relatively high conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of intelligent strain sensors, and in particular relates to an oxygen and moisture permeable strain sensor based on PVA and a preparation method thereof. Background Art

[0002] Strain sensors are usually devices that change the electrical and physical properties of the sensor, such as resistance, capacitance or inductance, based on the strain generated by the deformation of an object under force. The core component of a common strain sensor is generally a resistance strain gauge, which fits tightly to the object to be measured. When the object to be measured is deformed, the resistance strain gauge deforms accordingly, causing its resistance value to change significantly, thereby achieving the effect of strain sensing. In short, a strain sensor is a device that can convert strain into electrical signals of different intensities, thereby realizing the monitoring of strain and stress.

[0003] The material of the resistance strain gauge of the traditional strain sensor is generally metal foil, such as copper foil, nickel foil, aluminum foil, etc., which has the advantages of high sensitivity and good temperature stability. However, when applied to emerging technology fields such as wearable devices, strain sensors have higher requirements for the oxygen permeability and moisture permeability of resistance strain gauges. Strain sensors with metal foil as resistance strain gauges can no longer meet the requirements. Therefore, it is necessary to develop strain sensors with resistance strain gauges made of new materials. Summary of the invention

[0004] The present invention provides an oxygen and moisture permeable strain sensor based on PVA and a preparation method thereof, aiming to overcome the above-mentioned deficiencies in the prior art.

[0005] The technical solution of the present invention to solve the above technical problem is as follows: a method for preparing an oxygen and moisture permeable strain sensor based on PVA, comprising the following steps:

[0006] S1. Preparation of modified PVA raw material: 40-80 parts by weight of PVA powder, 10-20 parts by weight of modified bamboo powder, 3-5 parts by weight of graphene oxide and 1-3 parts of silane coupling agent are placed in a mixer and mixed, and then blended and extruded at 125-135 ° C to obtain a granular modified PVA raw material for standby use;

[0007] S2. Preparation of PVA dispersion: first, bamboo charcoal powder and polyacrylate type hyperdispersant are added to water, mixed and fully ground, filtered, and the modified PVA raw material is added to the filtrate, stirred and dissolved to obtain a PVA dispersion, which is set aside;

[0008] S3. Preparation of gel thin film resistor: PVA dispersion is placed in a mold with a thin layer cavity, and repeatedly frozen and thawed to obtain a thin layer of gel, and a polytetrafluoroethylene block is used to pressurize the thin layer of gel in a closed chamber and the humidity in the closed chamber is controlled to 25-35% for 10-24 hours to obtain a gel thin film resistor for standby use;

[0009] S4. In-situ conductivity enhancement: immerse the gel thin film resistor in an ethanol solution of thiophene derivatives and iodine, take it out after it is soaked, and naturally evaporate and dry it at room temperature for 3-5 hours. Then, place the gel thin film resistor under atmospheric pressure plasma for in-situ solid-state polymerization. After the polymerization is completed, the gel thin film resistor with enhanced conductivity is obtained and is ready for use;

[0010] S5. Electrode fixing: Print or stick conductive electrodes on both ends of the gel film resistor sheet prepared in S4 to obtain a PVA-based oxygen and moisture permeability strain sensor.

[0011] On the basis of the above technical solutions, the present invention can also make the following further specific options.

[0012] Specifically, the molecular weight of the PVA powder in S1 is between 100,000 and 130,000.

[0013] Specifically, the modified bamboo powder in S1 is polyethylene wax grafted maleic anhydride modified bamboo powder.

[0014] Specifically, the silane coupling agent in S1 is KH-550 or KH-560.

[0015] Specifically, the bamboo charcoal powder in S2 is an ultrafine powder with a particle size of less than 5 μm, and the weight ratio of the bamboo charcoal powder to the polyacrylate type superdispersant is 1:0.04-0.08.

[0016] Specifically, 4-8 g of modified PVA raw material is added to every 100 mL of filtrate in S2.

[0017] Specifically, the thickness of the thin layer of gel in S3 is 1.5-2.5 mm, and the thickness of the gel film resistor is 0.4-0.8 mm.

[0018] Specifically, the thiophene derivative in S4 is 2,2'-bithiophene or 3,3'-dibromo-2,2'-bithiophene, the concentration of the thiophene derivative in the ethanol solution is 1-2 mol / L, and the concentration of iodine is 0.8-1.5 mol / L.

[0019] Specifically, the conductive electrode in S5 is an aluminum foil electrode, a copper foil electrode or a conductive ink printed electrode.

[0020] The present invention also provides an oxygen and moisture permeability strain sensor based on PVA, which is prepared by the above method.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The invention uses PVA powder as a basic raw material, firstly obtains a modified PVA raw material by high-mixing and extruding modified bamboo powder, graphene oxide and silane coupling agent, thereby improving the water resistance, oxygen permeability and strength of PVA. Subsequently, the modified PVA raw material, bamboo charcoal powder and dispersant are dissolved in water to obtain a PVA dispersion, and a thin layer of gel is obtained after repeated freezing and thawing. The bamboo charcoal powder can not only significantly improve the strength of the gel but also enable it to have certain basic conductivity and adsorption performance. The humidity of the gel thin film resistor obtained after pressure application and humidity control is relatively low, so after being immersed in an ethanol solution, it can swell better and absorb the thiophene derivatives and iodine in the ethanol solution. After being taken out and dried, the ethanol small molecules are volatilized, and the thiophene derivatives and iodine remain in the gel layer in situ. Some thiophene derivatives and iodine are also adsorbed by bamboo charcoal powder. Then, under the action of atmospheric pressure plasma, the thiophene derivatives are in situ polymerized and doped with iodine to form polymer fibers with conductive ability. The polymer fibers make the bamboo charcoal powder originally distributed in an island shape electrically connected and physically entangled with each other, thereby significantly enhancing the conductivity and strength of the gel thin film resistor. After testing, the PVA-based oxygen permeable and moisture permeable strain sensor prepared by the present invention has high oxygen permeability and moisture permeability and has both suitable strength and high conductivity, overcoming the deficiency that the air permeability and oxygen permeability of the existing metal foil strain sensor cannot meet the use requirements. DETAILED DESCRIPTION

[0023] The principles and features of the present invention are described below in conjunction with specific embodiments. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0024] To avoid redundant description, the drugs used in the following examples are all commercially available products unless otherwise specified, and the methods used are all conventional methods in the art unless otherwise specified.

[0025] The molecular weight of the PVA powder in the following embodiments is between 100,000 and 130,000; the modified bamboo powder is polyethylene wax grafted maleic anhydride modified bamboo powder, and its preparation process is as follows: 100 parts of bamboo powder with a particle size of 100-200 mesh, 40 parts of maleic anhydride grafted polyethylene wax, 8 parts of maleic anhydride and 6 parts of zinc stearate are placed in a high-speed stirring mixer, first heated to 120° C., stirred at a speed of 820 r / min for 5 minutes, then heated to 125° C. and stirred at a speed of 2000 r / min for 25 minutes, and finally adjusted to 300 r / min and naturally cooled to room temperature to obtain the modified bamboo powder.

[0026] Example 1

[0027] A method for preparing an oxygen and moisture permeable strain sensor based on PVA, comprising the following steps:

[0028] S1. Preparation of modified PVA raw material: 40 parts by weight of PVA powder, 10 parts by weight of modified bamboo powder, 3 parts by weight of graphene oxide and 1 part of silane coupling agent KH-550 were placed in a mixer and mixed, and then blended and extruded at 125 ° C to obtain a granular modified PVA raw material for standby use;

[0029] S2. Preparation of PVA dispersion: first, add bamboo charcoal powder and polyacrylate type superdispersant into water, mix and fully grind, bamboo charcoal powder is ultrafine powder with a particle size of less than 5 μm, and the weight ratio of bamboo charcoal powder to polyacrylate type superdispersant is 1:0.04, filter, add modified PVA raw material to the filtrate, add 4 g of modified PVA raw material to every 100 mL of filtrate, stir and dissolve to obtain PVA dispersion, set aside;

[0030] S3. Preparation of gel thin film resistor: PVA dispersion is placed in a mold with a thin layer cavity, and repeatedly frozen and thawed for more than three times to obtain a thin layer gel, the thickness of the thin layer gel is 1.5 mm, and a polytetrafluoroethylene block is used to press the thin layer gel in a closed chamber, and dehumidification is performed to control the humidity in the closed chamber to 35% for 10 hours to obtain a gel thin film resistor, the thickness of the gel thin film resistor is 0.4 mm, and it is set aside;

[0031] S4. In-situ conductivity enhancement: immerse the gel thin film resistor in an ethanol solution of a thiophene derivative and iodine, wherein the thiophene derivative is 2,2'-bithiophene, the concentration of the thiophene derivative in the ethanol solution is 1 mol / L, and the concentration of iodine is 0.8 mol / L. After immersion for more than 5 hours, take it out, evaporate and dry it naturally at room temperature for 3 hours, and then place the gel thin film resistor under atmospheric pressure plasma for in-situ solid-state polymerization for 30 minutes. After the polymerization is completed, the gel thin film resistor with enhanced conductivity is obtained and is ready for use;

[0032] S5. Electrode fixing: Conductive electrodes (copper foil electrodes) are pasted on both ends of the gel film resistor obtained in S4 to obtain a PVA-based oxygen and moisture permeability strain sensor.

[0033] Example 2

[0034] A method for preparing an oxygen and moisture permeable strain sensor based on PVA, comprising the following steps:

[0035] S1. Preparation of modified PVA raw material: 60 parts by weight of PVA powder, 15 parts by weight of modified bamboo powder, 4 parts by weight of graphene oxide and 2 parts of silane coupling agent KH-550 were placed in a mixer and mixed, and then blended and extruded at 130 ° C to obtain a granular modified PVA raw material for standby use;

[0036] S2. Preparation of PVA dispersion: first, add bamboo charcoal powder and polyacrylate type superdispersant into water, mix and fully grind, bamboo charcoal powder is ultrafine powder with a particle size of less than 5 μm, and the weight ratio of bamboo charcoal powder to polyacrylate type superdispersant is 1:0.06, filter, add modified PVA raw material to the filtrate, add 6 g of modified PVA raw material to every 100 mL of filtrate, stir and dissolve to obtain PVA dispersion, set aside;

[0037] S3. Preparation of gel thin film resistor: PVA dispersion is placed in a mold with a thin layer cavity, and repeatedly frozen and thawed for more than three times to obtain a thin layer gel, the thickness of the thin layer gel is 2.0 mm, and a polytetrafluoroethylene block is used to press the thin layer gel in a closed chamber, and dehumidification is performed to control the humidity in the closed chamber to 30% for 18 hours to obtain a gel thin film resistor, the thickness of the gel thin film resistor is 0.6 mm, and it is set aside;

[0038] S4. In-situ conductivity enhancement: immerse the gel thin film resistor in an ethanol solution of a thiophene derivative and iodine, wherein the thiophene derivative is 2,2'-bithiophene, the concentration of the thiophene derivative in the ethanol solution is 1.5 mol / L, and the concentration of iodine is 1.2 mol / L. After immersion for more than 5 hours, take it out, evaporate and dry it naturally at room temperature for 4 hours, and then place the gel thin film resistor under atmospheric pressure plasma for in-situ solid-state polymerization for 30 minutes. After the polymerization is completed, the gel thin film resistor with enhanced conductivity is obtained and is ready for use;

[0039] S5. Electrode fixing: Conductive electrodes (copper foil electrodes) are pasted on both ends of the gel film resistor obtained in S4 to obtain a PVA-based oxygen and moisture permeability strain sensor.

[0040] Example 3

[0041] A method for preparing an oxygen and moisture permeable strain sensor based on PVA, comprising the following steps:

[0042] S1. Preparation of modified PVA raw material: 80 parts by weight of PVA powder, 20 parts by weight of modified bamboo powder, 5 parts by weight of graphene oxide and 3 parts of silane coupling agent KH-550 were placed in a mixer and mixed, and then blended and extruded at 135 ° C to obtain a granular modified PVA raw material for standby use;

[0043] S2. Preparation of PVA dispersion: first, add bamboo charcoal powder and polyacrylate type superdispersant into water, mix and fully grind, bamboo charcoal powder is ultrafine powder with a particle size of less than 5 μm, and the weight ratio of bamboo charcoal powder to polyacrylate type superdispersant is 1:0.08. Filter, add modified PVA raw material to the filtrate, add 8 g of modified PVA raw material to every 100 mL of filtrate, stir and dissolve to obtain PVA dispersion, and set aside;

[0044] S3. Preparation of gel thin film resistor: PVA dispersion is placed in a mold with a thin layer cavity, and repeatedly frozen and thawed for more than three times to obtain a thin layer gel, the thickness of the thin layer gel is 2.5 mm, and a polytetrafluoroethylene block is used to press the thin layer gel in a closed chamber, and dehumidification is performed to control the humidity in the closed chamber to 25% for 22 hours to obtain a gel thin film resistor, the thickness of the gel thin film resistor is 0.8 mm, and it is set aside;

[0045] S4. In-situ conductivity enhancement: immerse the gel thin film resistor in an ethanol solution of a thiophene derivative and iodine, wherein the thiophene derivative is 2,2'-bithiophene, the concentration of the thiophene derivative in the ethanol solution is 2 mol / L, and the concentration of iodine is 1.5 mol / L. After immersion for more than 5 hours, take it out, evaporate and dry it naturally at room temperature for 5 hours, and then place the gel thin film resistor under atmospheric pressure plasma for in-situ solid-state polymerization for 30 minutes. After the polymerization is completed, the gel thin film resistor with enhanced conductivity is obtained and is ready for use;

[0046] S5. Electrode fixing: Conductive electrodes (copper foil electrodes) are pasted on both ends of the gel film resistor obtained in S4 to obtain a PVA-based oxygen and moisture permeability strain sensor.

[0047] Example 4

[0048] A method for preparing an oxygen and moisture permeable strain sensor based on PVA, comprising the following steps:

[0049] S1. Preparation of modified PVA raw material: 48 parts by weight of PVA powder, 12 parts by weight of modified bamboo powder, 3.2 parts by weight of graphene oxide and 1.2 parts of silane coupling agent KH-550 were placed in a mixer and mixed, and then blended and extruded at 128 ° C to obtain a granular modified PVA raw material for standby use;

[0050] S2. Preparation of PVA dispersion: first, add bamboo charcoal powder and polyacrylate type superdispersant into water, mix and fully grind, bamboo charcoal powder is ultrafine powder with a particle size of less than 5 μm, and the weight ratio of bamboo charcoal powder to polyacrylate type superdispersant is 1:0.05, filter, add modified PVA raw material to the filtrate, add 5 g of modified PVA raw material to every 100 mL of filtrate, stir and dissolve to obtain PVA dispersion, set aside;

[0051] S3. Preparation of gel thin film resistor: PVA dispersion is placed in a mold with a thin layer cavity, and repeatedly frozen and thawed for more than three times to obtain a thin layer gel, the thickness of the thin layer gel is 1.6 mm, and a polytetrafluoroethylene block is used to press the thin layer gel in a closed chamber, and dehumidification is performed to control the humidity in the closed chamber to 32% for 12 hours to obtain a gel thin film resistor, the thickness of the gel thin film resistor is 0.5 mm, and it is set aside;

[0052] S4. In-situ conductivity enhancement: immerse the gel thin film resistor in an ethanol solution of a thiophene derivative and iodine, wherein the thiophene derivative is 2,2'-bithiophene, the concentration of the thiophene derivative in the ethanol solution is 1.2 mol / L, and the concentration of iodine is 0.9 mol / L. After immersion for more than 5 hours, take it out, evaporate and dry it naturally at room temperature for 3 hours, and then place the gel thin film resistor under atmospheric pressure plasma for in-situ solid-state polymerization for 30 minutes. After the polymerization is completed, the gel thin film resistor with enhanced conductivity is obtained and is ready for use;

[0053] S5. Electrode fixing: Conductive electrodes (copper foil electrodes) are pasted on both ends of the gel film resistor obtained in S4 to obtain a PVA-based oxygen and moisture permeability strain sensor.

[0054] Example 5

[0055] A method for preparing an oxygen and moisture permeable strain sensor based on PVA, comprising the following steps:

[0056] S1. Preparation of modified PVA raw material: 66 parts by weight of PVA powder, 16 parts by weight of modified bamboo powder, 4.1 parts by weight of graphene oxide and 2.4 parts of silane coupling agent KH-550 were placed in a mixer and mixed, and then blended and extruded at 130 ° C to obtain a granular modified PVA raw material for standby use;

[0057] S2. Preparation of PVA dispersion: first, add bamboo charcoal powder and polyacrylate type superdispersant into water, mix and fully grind, bamboo charcoal powder is ultrafine powder with a particle size of less than 5 μm, and the weight ratio of bamboo charcoal powder to polyacrylate type superdispersant is 1:0.06, filter, add modified PVA raw material to the filtrate, add 6 g of modified PVA raw material to every 100 mL of filtrate, stir and dissolve to obtain PVA dispersion, set aside;

[0058] S3. Preparation of gel thin film resistor: PVA dispersion is placed in a mold with a thin layer cavity, and repeatedly frozen and thawed for more than three times to obtain a thin layer gel, the thickness of the thin layer gel is 1.8 mm, and a polytetrafluoroethylene block is used to press the thin layer gel in a closed chamber, and dehumidification is performed to control the humidity in the closed chamber to 28% for 20 hours to obtain a gel thin film resistor, the thickness of the gel thin film resistor is 0.6 mm, and it is set aside;

[0059] S4. In-situ conductivity enhancement: immerse the gel thin film resistor in an ethanol solution of a thiophene derivative and iodine, wherein the thiophene derivative is 2,2'-bithiophene, the concentration of the thiophene derivative in the ethanol solution is 1.4 mol / L, and the concentration of iodine is 1.3 mol / L. After immersion for more than 5 hours, take it out, evaporate and dry it naturally at room temperature for 4 hours, and then place the gel thin film resistor under atmospheric pressure plasma for in-situ solid-state polymerization for 30 minutes. After the polymerization is completed, the gel thin film resistor with enhanced conductivity is obtained and is ready for use;

[0060] S5. Electrode fixing: Conductive electrodes (copper foil electrodes) are pasted on both ends of the gel film resistor obtained in S4 to obtain a PVA-based oxygen and moisture permeability strain sensor.

[0061] Example 6

[0062] A method for preparing an oxygen and moisture permeable strain sensor based on PVA, comprising the following steps:

[0063] S1. Preparation of modified PVA raw material: 75 parts by weight of PVA powder, 18 parts by weight of modified bamboo powder, 4.8 parts by weight of graphene oxide and 3 parts of silane coupling agent KH-550 were placed in a mixer and mixed, and then blended and extruded at 132 ° C to obtain a granular modified PVA raw material for standby use;

[0064] S2. Preparation of PVA dispersion: first, add bamboo charcoal powder and polyacrylate type superdispersant into water, mix and fully grind, bamboo charcoal powder is ultrafine powder with a particle size of less than 5 μm, and the weight ratio of bamboo charcoal powder to polyacrylate type superdispersant is 1:0.07, filter, add modified PVA raw material to the filtrate, add 7 g of modified PVA raw material to every 100 mL of filtrate, stir and dissolve to obtain PVA dispersion, set aside;

[0065] S3. Preparation of gel thin film resistor: PVA dispersion is placed in a mold with a thin layer cavity, and repeatedly frozen and thawed for more than three times to obtain a thin layer gel, the thickness of the thin layer gel is 2 mm, and a polytetrafluoroethylene block is used to press the thin layer gel in a closed chamber, and dehumidification is performed to control the humidity in the closed chamber to 26% for 24 hours to obtain a gel thin film resistor, the thickness of the gel thin film resistor is 0.7 mm, and it is set aside;

[0066] S4. In-situ conductivity enhancement: immerse the gel thin film resistor in an ethanol solution of a thiophene derivative and iodine, wherein the thiophene derivative is 2,2'-bithiophene, the concentration of the thiophene derivative in the ethanol solution is 1.8 mol / L, and the concentration of iodine is 1.4 mol / L. After immersion for more than 5 hours, take it out, evaporate and dry it naturally at room temperature for 5 hours, and then place the gel thin film resistor under atmospheric pressure plasma for in-situ solid-state polymerization for 30 minutes. After the polymerization is completed, the gel thin film resistor with enhanced conductivity is obtained and is ready for use;

[0067] S5. Electrode fixing: Conductive electrodes (copper foil electrodes) are pasted on both ends of the gel film resistor obtained in S4 to obtain a PVA-based oxygen and moisture permeability strain sensor.

[0068] Comparative Example 1

[0069] The only difference between this comparative example and Example 1 is that modified bamboo powder is not used in S1.

[0070] Comparative Example 2

[0071] The only difference between this comparative example and Example 1 is that graphene oxide is not used in S1.

[0072] Comparative Example 3

[0073] The only difference between this comparative example and Example 1 is that bamboo charcoal powder and polyacrylate type hyperdispersant are not used in S2, but the modified PVA raw material is directly dissolved in water, and the amount used is equivalent to that in Example 1.

[0074] Comparative Example 4

[0075] The only difference between this comparative example and Example 1 is that step S4 is missing, and copper foil electrodes are directly pasted and fixed after the gel film resistor is prepared in step S3.

[0076] The strain sensors obtained in Examples 1 to 6 were used as test objects to measure physical properties such as moisture permeability, oxygen permeability, tensile strength and conductivity. The results showed that the moisture permeability of the strain sensors obtained in Examples 1 to 6 was 400 g / m 2 · More than one day, oxygen permeability 2000mL / m 2 ·day·atm, the tensile strength is about 8.5-12.5MPa, and the conductivity is about 0.3-1.0S / m. It can be seen that the PVA-based oxygen and moisture permeability strain sensor prepared by the present invention has high oxygen and moisture permeability and has both suitable strength and high conductivity. At the same time, after a certain stress is applied to pull the strain sensor, the test shows that the conductivity caused by the strain changes significantly, that is, it has a high strain sensitivity.

[0077] In addition, the corresponding physical parameters of Examples 1 to 4 were tested. The results showed that in Example 1, since no modified bamboo powder was added, the actual tensile strength was only about 3.1 MPa, which was relatively poor. At the same time, since there was no modified bamboo powder to enhance its moisture and oxygen permeability, the moisture permeability of the corresponding strain sensor was less than 100 g / m 2 day, the oxygen permeability is only about 500mL / m 2·day·atm, and the water resistance of the strain sensor is significantly deteriorated; in Comparative Example 2, since graphene oxide is not used, the mutual dispersibility of PVA powder and bamboo powder is deteriorated, and the water solubility and water resistance of the modified PVA raw material are also significantly reduced, and the moisture permeability and oxygen permeability of the strain sensor finally obtained are reduced by about 20% and 13%, respectively; in Comparative Example 3, bamboo charcoal powder and polyacrylate type hyperdispersant are not used, resulting in a serious decrease in the tensile strength and conductivity of the obtained strain sensor, with a tensile strength of about 4.5Mpa and a conductivity of only about 0.008S / m; in Comparative Example 4, due to the lack of step S4, the tensile strength, conductivity, oxygen permeability and moisture permeability of the obtained strain sensor are all reduced to varying degrees relative to Example 1, wherein the tensile strength is about 6.7MPa, the conductivity is about 0.08S / m, the moisture permeability is reduced by about 8%, and the oxygen permeability is reduced by about 11%.

[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an oxygen and moisture permeable strain sensor based on PVA, characterized in that: The steps include: S1. Preparation of modified PVA raw material: 40-80 parts by weight of PVA powder, 10-20 parts by weight of modified bamboo powder, 3-5 parts by weight of graphene oxide and 1-3 parts of silane coupling agent are placed in a mixer and mixed, and then blended and extruded at 125-135 ° C to obtain a granular modified PVA raw material for standby use; S2. Preparation of PVA dispersion: first, bamboo charcoal powder and polyacrylate type hyperdispersant are added to water, mixed and fully ground, filtered, and the modified PVA raw material is added to the filtrate, stirred and dissolved to obtain a PVA dispersion, which is set aside; S3. Preparation of gel thin film resistor: PVA dispersion is placed in a mold with a thin layer cavity, and repeatedly frozen and thawed to obtain a thin layer of gel, and a polytetrafluoroethylene block is used to pressurize the thin layer of gel in a closed chamber and the humidity in the closed chamber is controlled to 25-35% for 10-24 hours to obtain a gel thin film resistor for standby use; S4. In-situ conductivity enhancement: immerse the gel thin film resistor in an ethanol solution of thiophene derivatives and iodine, take it out after it is soaked, and naturally evaporate and dry it at room temperature for 3-5 hours. Then, place the gel thin film resistor under atmospheric pressure plasma for in-situ solid-state polymerization. After the polymerization is completed, the gel thin film resistor with enhanced conductivity is obtained and is ready for use; S5. Electrode fixing: Print or stick conductive electrodes on both ends of the gel film resistor sheet prepared in S4 to obtain a PVA-based oxygen and moisture permeability strain sensor.

2. The method for preparing a PVA-based oxygen and moisture permeable strain sensor according to claim 1, characterized in that: The molecular weight of the PVA powder in S1 is between 100,000 and 130,000.

3. The method for preparing a PVA-based oxygen and moisture permeable strain sensor according to claim 1, characterized in that: The modified bamboo powder in S1 is polyethylene wax grafted maleic anhydride modified bamboo powder.

4. The method for preparing a PVA-based oxygen and moisture permeable strain sensor according to claim 1, characterized in that: The silane coupling agent in S1 is KH-550 or KH-560.

5. The method for preparing a PVA-based oxygen and moisture permeable strain sensor according to claim 1, characterized in that: The bamboo charcoal powder in S2 is an ultrafine powder with a particle size of less than 5 μm, and the weight ratio of the bamboo charcoal powder to the polyacrylate type superdispersant is 1:0.04-0.

08.

6. The method for preparing a PVA-based oxygen and moisture permeable strain sensor according to claim 1, characterized in that: In S2, 4-8 g of modified PVA raw material was added to every 100 mL of filtrate.

7. The method for preparing a PVA-based oxygen and moisture permeable strain sensor according to claim 1, characterized in that: The thickness of the thin layer of gel in S3 is 1.5-2.5 mm, and the thickness of the gel film resistor is 0.4-0.8 mm.

8. The method for preparing a PVA-based oxygen and moisture permeable strain sensor according to claim 1, characterized in that: The thiophene derivative in S4 is 2,2'-bithiophene or 3,3'-dibromo-2,2'-bithiophene, the concentration of the thiophene derivative in the ethanol solution is 1-2 mol / L, and the concentration of iodine is 0.8-1.5 mol / L.

9. The method for preparing a PVA-based oxygen and moisture permeable strain sensor according to any one of claims 1 to 8, characterized in that: The conductive electrode in S5 is an aluminum foil electrode, a copper foil electrode or a conductive ink printed electrode.

10. A PVA-based oxygen and moisture permeability strain sensor, characterized in that: It is prepared by the method according to any one of claims 1 to 9.